Prevalence of Burkholderia cepacia recovered from clinical specimens at tertiary care hospital - Kumar, Amit; Gupta, Shilpi; Saban, Prachi; Patanvadia, Dipak; Deskar, Deepak; Kishori, Rekha; Pargi, Pankti (International Journal of Advances in Medicine, 2025)
Background: One of the multiple intrinsically resistant bacteria that cause opportunistic illnesses is Burkholderia cepacia. The distribution of B. cepacia isolates according to clinical specimen categories, hospital wards, patient gender and age, and antibiotic susceptibility assessment were the main objectives of the study. Methods: This hospital based cross sectional study was conducted in department of microbiology at SAIMS Indore M. P. from May 2024 to June 2024. Relevant samples for e. g., blood, urine, sputum, body fluids, pus were collected as per institution collection protocol from inpatient and outpatient department. Results: A total of 4875 clinical samples received for culture, 1738 samples were found positive of which 100 (2.015%) B. cepacia were isolated from various clinical samples (Table 1 and Figure 4). The majority of the 100 B. cepacia isolates were isolated from blood and respiratory samples (sputum, bronchoalveolar lavage, pleural fluid), followed by pus and urine samples, which accounted for 80 (80%), 12 (12%), 7 (7%) and 1 (1%) isolate, respectively. Conclusions: B. cepacia is emerging cause of various clinical manifestations including septicemia with multi drug resistance that need to be treated quickly and effectively.